Faktor-Faktor Penyebab Rendahnya Karakter Disiplin Siswa Kelas X IPS di SMA Negeri 1 Junjung Sirih - Ghandy Putra Ananda; Desri Nora (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This research is motivated by the occurrence of various problems with the character of discipline in SMA Negeri 1 Junjung Sirih, especially among students of class X Social Sciences. Problems with the character of discipline, such as students not obeying the rules that apply at school and the low attendance list of class X IPS students during the Covid-19 pandemic. This makes the researcher ask what factors cause the low discipline character of class X IPS students at SMA Negeri 1 Junjung Sirih. The study aimed to explain the factors causing the low discipline character of class X Social Studies students of SMA Negeri 1 Junjung Sirih. To analyze the problem of this research, the researcher used Structural Functional Theory from Talcott Parsons to analyze this research. The research method used is a qualitative method with the type of case study, and the informant selection technique uses purposive sampling with a total of 16 informants. In-depth interviews carry out data collection, observations, and documents—data analysis using the Miles and Huberman interactive analysis technique. Based on the results of the research that the researchers got at SMA Negeri 1 Junjung Sirih, it can be concluded that the factors causing the low character of students' discipline are internal factors such as the lack of awareness of students and low self-motivation of students. In contrast, the external factors are teacher factors such as socialization. Regulations to students, habits, and character of teacher discipline in schools, and inconsistent teachers in giving punishment to students, while environmental factors are the school environment that has not been fully fenced, and road access to schools is less supportive.